Application de la méthode AIR avec la BD Marsupilami comme support d’apprentissage de compréhension écrite - Viranty Indryani; Ria Fitrasih (Universitas Negeri Semarang, 2025)
The AIR method (Audience, Intellectual, Repetition) is a learning model considered suitable for the reading skills of advanced students. This study aims 1) to describe the application of the AIR method (Auditory, Intellectually and Repetition) with the Marsupilami comic strip as a means of learning advanced students’ French reading skills, 2) to describe the effectiveness of applying the AIR method with the Marsupilami comic strip as a means of learning advanced students’ French reading skills. This research is a descriptive-qualitative pre-experiment, a one-shot case study design. The subjects of this study were students in the 5th semester of the Advanced Written French course, a total of 25 students. Data collection techniques included observation, testing and documentation. The results showed that applying the AIR method with Marsupilami comics as a means of teaching advanced students French reading skills was not effective. The research results showed that 18 students, or 72% of the students, achieved the full score or reached the score of 65. This means that the percentage of learning results is less than 85%, and that we can say that the application of the method in learning French is not effective.